Detection of Heavy Metals Based on Boron-doped Diamond Nanograss Array, Boron-doped Diamond Film and Glassy Carbon Electrodes - Wei, Min; Ying Zeng, Gao; Liu, Yong; Lu, Qiyu (Asian Journal of Chemistry, 2012)
In this work, boron-doped diamond nanograss array, boron-doped diamond film and GC electrode were used to investigate the voltammetric response of Cd2+ and determination of the mixture of Cd2+, Pb2+ and Cu2+ with differential pulse stripping voltammetry. For the stripping of Cd, although GC electrode was slightly better than boron-doped diamond nanograss array and boron-doped diamond film electrode in terms of peak current response, the reproducibility of boron-doped diamond nanograss array electrode was superior to that of boron-doped diamond film and GC electrode. In case of determination of the mixture of Cd2+, Pb2+ and Cu2+, boron-doped diamond nanograss array electrode provided better analytical detection when compared to boron-doped diamond film and GC electrode. These results demonstrated that the boron-doped diamond nanograss array electrode was quite satisfactory with less surface adsorption, better reproducibility and higher resolution.